Core/shell nanofibers with embedded liposomes as a drug delivery system - Mickova, Andrea; Buzgo, Matej; Benada, Oldrich; Rampichova, Michala; Fisar, Zdenek; Filova, Eva; Tesarova, Martina; Lukas, David; Amler, Evzen (Biomacromolecules, 2012)
The broader application of liposomes in regenerative medicine is hampered by their short half-life and inefficient retention at the site of application. These disadvantages could be significantly reduced by their combination with nanofibers. We produced 2 different nanofiber-liposome systems in the present study, that is, liposomes blended within nanofibers and core/shell nanofibers with embedded liposomes. Herein, we demonstrate that blend electrospinning does not conserve intact liposomes. In contrast, coaxial electrospinning enables the incorporation of liposomes into nanofibers. We report polyvinyl alcohol-core/poly-ε-caprolactone-shell nanofibers with embedded liposomes and show that they preserve the enzymatic activity of encapsulated horseradish peroxidase. The potential of this system was also demonstrated by the enhancement of mesenchymal stem cell proliferation. In conclusion, intact liposomes incorporated into nanofibers by coaxial electrospinning are very promising as a drug delivery system.
Keywords: povrchové vlastnosti; viabilita buněk; Particle Size; Cell Proliferation; Liposomes; Cell Survival; Drug Carriers; liposomy; Drug Delivery Systems; lidé; nanovlákna; Humans; velikost částic; Surface Properties; Nanofibers; Horseradish Peroxidase; proliferace buněk; křenová peroxidasa; nosiče léků; Mesenchymal Stem Cells; lékové transportní systémy; mezenchymální kmenové buňky